Polygamy and the Ethics of Transparency in Muhammad Syahrur’s Theory of Limits: An Analysis of Indonesia’s 2025 Viral Cases - Muflihah, Iefah; Alfariz, Ardan; Rosa, Andi (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2025)
The emergence of viral cases of non-transparent polygamy in Indonesia in 2025 has reignited critical debates on family ethics, honesty, and moral accountability in contemporary Muslim societies. This study examines these practices through the lens of Muhammad Syahrur’s Theory of Limits (Naẓariyyat al-Ḥudūd), which conceptualizes Islamic legal norms as operating within defined minimum and maximum ethical boundaries. Employing a qualitative research design, this study is based on a critical literature review combined with intra-textual analysis of Qur’anic verses on marriage and polygamy, alongside an examination of Syahrur’s principal works. Sociological data from publicly documented viral cases are utilized as contextual evidence to illustrate the ethical tensions surrounding non-transparent polygamy. The findings demonstrate that, within Syahrur’s framework, polygamy is not an unconditional male prerogative but a conditional social practice constrained by strict moral limits aimed at safeguarding justice and protecting women’s rights. Polygamy conducted without transparency is shown to violate the minimum boundary of justice by denying women access to truthful information, undermining trust, and generating psychological and social harm. From the perspective of boundary theory, such practices constitute a form of injustice (ẓulm) and conflict with the maqāṣid al-sharīʿah, particularly the preservation of dignity, welfare, and family stability. This study argues that Syahrur’s Theory of Limits offers a relevant ethical framework for evaluating modern polygamy, emphasizing transparency, honesty, and justice as indispensable principles in contemporary Islamic family ethics.